Seed coat micromorphology of South American species of Hybanthus (Violaceae) - Seo, Micaela Noemi (2010)
The seed-coat of several species of Hybanthus subg. Ionidium from South America were studied by SEM (scanning electronic microscopy). Three different levels of sculpture were observed on the seed coat. The micro-morphological patterns showed great variation between the species and should be considered as additional characters in future taxonomic treatments. The presence of a conspicuous elaiosome was observed; this structure is well known in the genus Viola and is most likely related to seed dispersal mediated by ants. © 2010 The Authors.